Pengaruh Konsentrasi Ekstrak Jeruk Nipis (Citrus Aurantiifolia) Terhadap Mutu Granul Dan Tablet Effervescent - Kiki Rizki Handayani; Putri, Tiara Alnelya; Unaisah (Jurnal Kesehatan Madani Medika, 2025)
Lime (Citrus aurantiifolia) is a fruit rich in vitamin C, which plays an important role in enhancing immune function. In this study, lime extract was utilized as an active ingredient due to its immunostimulant properties that help strengthen the body’s defense system. Lime-flavored effervescent tablets represent an innovative pharmaceutical dosage form that is practical, appealing in taste and appearance, and may increase consumer compliance. This dosage form also provides a refreshing effect resulting from the acid–base reaction that produces carbon dioxide (CO₂). This experimental study formulated four lime effervescent granule formulations with varying extract concentrations (0%, 6.25%, 12.5%, and 18.75%) using the wet granulation method. The granules were evaluated for organoleptic properties, particle size distribution, flow rate, angle of repose, compressibility, pH, and dissolution rate. Tablet evaluation included organoleptic assessment, weight uniformity, size uniformity, and disintegration time. The data were analyzed using SPSS software with a one-way analysis of variance (ANOVA). The results showed that all three formulations containing lime extract demonstrated good physical quality of the granules, with formulation F3 producing effervescent tablets of the best physical quality.